2016
DOI: 10.1093/neuonc/nov313
|View full text |Cite
|
Sign up to set email alerts
|

Von Hippel-Lindau disease: an evaluation of natural history and functional disability

Abstract: Our study defines the disease progression and provides a comprehensive view of the syndrome over time. We analyzed for the first time the functional disability of VHL patients, assessing the progression for each function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 27 publications
2
42
1
2
Order By: Relevance
“…The sex differences are especially evident for VHL missense mutation carriers, where the female death rates were almost five times as high as the male. The influence of sex on vHL natural history has previously been explored 8 9 15 25. Consistent with our results, one study found a poorer life expectancy for female patients compared with male (median life expectancy: men: 59.4 years (n=35)/women: 48.4 years (n=33)) 9.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The sex differences are especially evident for VHL missense mutation carriers, where the female death rates were almost five times as high as the male. The influence of sex on vHL natural history has previously been explored 8 9 15 25. Consistent with our results, one study found a poorer life expectancy for female patients compared with male (median life expectancy: men: 59.4 years (n=35)/women: 48.4 years (n=33)) 9.…”
Section: Discussionsupporting
confidence: 91%
“…The fact that all deaths among patients born after 1955 were vHL-related, and almost all were caused by CNS hemangioblastomas, is in part due to the low age of many patients in this group, but it also underlines the importance of the ongoing development of improved treatment options, both pharmacological, and surgical 2. Particularly, CNS hemangioblastoma treatment entails substantial risks of sequelae and perioperative/postoperative death 25. Many of the deaths classified as being CNS-related in our cohort (59%, 16 of 27) occurred during CNS surgery or due to long-term postoperative sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…12). In addition, surgical intervention for tumors may be associated with operative/postoperative complications, such as hemorrhage from a large CNS hemangioblastoma (13).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, VHL is divided into two major variants, namely type 1 and 2 (without and with phaeochromocytoma respectively); the latter is further divided into subtypes 2A (without renal cell carcinoma), 2B (with renal cell carcinoma) and 2C (phaeochromocytoma alone). The initial manifestations usually present in the third or fourth decade of life, and patients may suffer from severe disabilities such as blindness, hearing problems, and postsurgical complications of pancreatic or adrenal insufficiency. Around 15–30 per cent of patients with VHL develop phaeochromocytomas, of which 40–50 per cent are bilateral.…”
Section: Vhl Mutations In Von Hippel–lindau Diseasementioning
confidence: 99%
“…The initial manifestations usually present in the third or fourth decade of life, and patients may suffer from severe disabilities such as blindness, hearing problems, and postsurgical complications of pancreatic or adrenal insufficiency. Around 15–30 per cent of patients with VHL develop phaeochromocytomas, of which 40–50 per cent are bilateral.…”
Section: Vhl Mutations In Von Hippel–lindau Diseasementioning
confidence: 99%